PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY PADA PEMBELAJARAN 1 SUBTEMA KETERATURAN YANG MENAJUBKAN - Ayu Winda Sari; Teti Rostikawati; Ratih Purnamasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to develop an augmented reality-based learning video in learning 1 Sub-theme of Amazing Regularity. The method of this reserch and development uses ADDIE type (Analyze, Design, Development, Implementation, and Evaluation). This research involved one teacher as a media, material, and language expert. In brief, this study also involved two expert judgment validators. The population and sample in this study were class VI students at SDN Semplak 1 Bogor in the academic year 2021 / 2022 with a total of 28 students. The instruments used in this study consisted of expert validation sheets, student questionnaire sheets, and student evaluation sheets. Based on the average results of the validation carried out by the validator, the expert media average was 90.5%, the linguist average was 92.5%, and the material expert was 90%. Augmented reality-based interactive learning video media also have been effective in increasing the learning motivation of class VI students by 79% in the excellent category and 21% in the good category.